Inclusive practices faced the risk of socio-educative exclusion. collaborative work structures in schools located in areas of social deprivation - F. Javier Amores; Maximiliano Ritacco (Universidad Autónoma de Madrid, 2012)
The study presented here was performed in three schools located in areas of social deprivation in order to identify dynamics with students at risk of school failure in the key of inclusive practices. For this, the used approach proposed answer the following question ¿Is it possible to identify and document inclusive practices that respond and be part of an active policy against the educational exclusion? In order to address this question, we used a qualitative research approach designed to identify inclusive practices looking for to capture, through an interpretive approach, the meanings that are built into school in disadvantaged contexts, and thus, to able to understand the relationships and meanings of the subjects actions in these centers. The data collection instruments included:-guides for the analysis of official data and documents-and -depth interviews. The methodological categorization process led us to the study results may respond positively to the possibility of identifying inclusive practices. In turn, one of the emerging categories more referenced pointed to the inclusive practices based on collaborative work structures. Within this we differ the following sub-categories: 1) collaborative structures of the school with the context and 2) collaborative structures in the school. Among the major conclusions we highlight those inclusive practices that are supported by a collaborative structure to realize, in time, a more equitable education with fewer fractures and differences for the most disadvantaged people.